2019
DOI: 10.1021/acsanm.9b00860
|View full text |Cite
|
Sign up to set email alerts
|

Solution Processed Highly Responsive UV Photodetectors from Carbon Nanodot/Silicon Heterojunctions

Abstract: Carbon nanostructures technology has recently emerged as a key enabler for next-generation optoelectronic devices working in the deep UV region due to their excitonic absorption. Here, we report the fabrication of “orange juice” derived solution processed carbon nanodots (CNDs)/n-Si heterojunction showing broadband spectral response with a peak responsivity of ∼1.25 A/W in UV (∼300 nm) wavelength. The surface topography and chemical information on synthesized CNDs via a facile synthesis route have been charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Unprecedented multifunctional devices can be designed by synergistically integrating various functional materials at the nanoscale range while maintaining their distinct properties. Moreover, exploring how the memristor device can be tuned with external stimuli, such as temperature, light, magnetic fields, mechanical stress, and many more, would be intriguing. , This exploration promises to enhance our understanding of memristor behavior and the complexities of neural interactions with the surrounding environment. Among all stimuli, light stands out as the most crucial factor for remotely tuning the RS behavior, opening the doors to the development of futuristic optofunctional devices. , In addition, ultraviolet (UV) photodetectors have numerous uses in optical communications, environmental exploration, ozone-layer monitoring, water purification, and chemical and biological investigations. The fundamental aspects of designing UV-regulated RS memory will be a unique approach for multiple futuristic applications. Such a technology allows the controllability of resistance using both voltage and UV-light pulses.…”
Section: Introductionmentioning
confidence: 99%
“…Unprecedented multifunctional devices can be designed by synergistically integrating various functional materials at the nanoscale range while maintaining their distinct properties. Moreover, exploring how the memristor device can be tuned with external stimuli, such as temperature, light, magnetic fields, mechanical stress, and many more, would be intriguing. , This exploration promises to enhance our understanding of memristor behavior and the complexities of neural interactions with the surrounding environment. Among all stimuli, light stands out as the most crucial factor for remotely tuning the RS behavior, opening the doors to the development of futuristic optofunctional devices. , In addition, ultraviolet (UV) photodetectors have numerous uses in optical communications, environmental exploration, ozone-layer monitoring, water purification, and chemical and biological investigations. The fundamental aspects of designing UV-regulated RS memory will be a unique approach for multiple futuristic applications. Such a technology allows the controllability of resistance using both voltage and UV-light pulses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, UV bandpass filters that can selectively transmit UV light are often combined with Si photodetectors, which will lead to an increased fabrication cost . On the other hand, some materials and light-trapping structures that can significantly enhance UV absorption are also used to improve the photoresponse of UV light. , However, these approaches are unfortunately not compatible with conventional Si manufacturing technology.…”
Section: Introductionmentioning
confidence: 99%
“…23 On the other hand, some materials and light-trapping structures that can significantly enhance UV absorption are also used to improve the photoresponse of UV light. 24,25 However, these approaches are unfortunately not compatible with conventional Si manufacturing technology.…”
Section: ■ Introductionmentioning
confidence: 99%
“…VOG, a vertical structure formed by the overlap of longitudinally grown graphene films, not only possesses similar electrical characteristics as graphene films but also exhibits excellent light absorption from the near-infrared (NIR) to infrared (IR) region because of the edge effects and uniform index of refraction at the interface. The unique structural/electrical properties of VOG are advantageous to the transport of photo-generated carriers and decrease recombination on the surface . Direct growth of VOG on arbitrary substrates by plasma-assisted chemical vapor deposition (PACVD) ensures the high quality of Schottky junction and improves the device performance. , Besides, GQDs as a novel class of carbon nanomaterials have undergone tremendous development in the past few years because of the unique electronic, optical, and chemical properties in conjunction with quantum confinement and edge effects. , Compared to traditional graphene derivatives, the enhanced solubility of GQDs is ideal for solution processing, thus boosting the production yields. It has been reported that GQDs contribute to light absorption and electron transportation of optoelectrical devices. , Therefore, the combination of GQDs and VOG may produce synergistic effects in light absorption and electron transportation to improve device performance .…”
Section: Introductionmentioning
confidence: 99%
“…18,21 Besides, GQDs as a novel class of carbon nanomaterials have undergone tremendous development in the past few years because of the unique electronic, optical, and chemical properties in conjunction with quantum confinement and edge effects. 22,23 Compared to traditional graphene derivatives, the enhanced solubility of GQDs is ideal for solution processing, thus boosting the production yields. It has been reported that GQDs contribute to light absorption and electron transportation of optoelectrical devices.…”
Section: ■ Introductionmentioning
confidence: 99%